GAMBARAN PERSALINAN DENGAN PRESENTASI BOKONG DI RSUD DR. SOEDARSO TAHUN 2008 - 2010 - ., Heristanto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Breech presentation is the highest number ofmalpresentation compared to other presentations. Determination of breechdelivery is still controversial, vaginal delivery are associated with a highnumber of perinatal morbidity and mortality compared to caesareansection delivery. In this case, the number of caesarean section hadincreasing in some recent decades in order to reducing that morbidity andmortality number.